2021
DOI: 10.3389/fpls.2021.658836
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Visualization With Multicolored Fluorescent Markers in Bamboo

Abstract: Bamboo is an important model plant to study the molecular mechanisms of rapid shoot growth and flowering once in a lifetime. However, bamboo research about protein functional characterization is largely lagged behind, mainly due to the lack of gene transformation platforms. In this study, a protoplast transient gene expression system in moso bamboo has been first established. Using this reliable and efficient system, we have generated a set of multicolored fluorescent markers based on the targeting sequences f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 110 publications
0
4
0
Order By: Relevance
“…Currently, investigation of subcellular protein localization in most crops primarily relies on heterologous transient expression systems, such as onion epidermal cells, Arabidopsis leaf protoplasts, rice leaf protoplasts, or tobacco leaves. However, due to the potentially limited conservation in protein sequences and regulatory factors governing protein trafficking within these heterologous expression systems, there is a risk of engendering spurious subcellular localization results in such approaches [ 27 29 ]. In this study, we infiltrated various organelle markers labeled with GFP or RFP, including those for ER ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, investigation of subcellular protein localization in most crops primarily relies on heterologous transient expression systems, such as onion epidermal cells, Arabidopsis leaf protoplasts, rice leaf protoplasts, or tobacco leaves. However, due to the potentially limited conservation in protein sequences and regulatory factors governing protein trafficking within these heterologous expression systems, there is a risk of engendering spurious subcellular localization results in such approaches [ 27 29 ]. In this study, we infiltrated various organelle markers labeled with GFP or RFP, including those for ER ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, as Arabidopsis is not an oil-producing plant, further research is needed to investigate the network mechanism of CcCLO1 in lipid accumulation, specifically in Chinese hickory or pecan. Additionally, ectopic expression of proteins in different plant species may result in mis-localization [44], necessitating enhancements to the transient transformation system for hickory. Currently, we are employing the procedures outlined in our previous study on bamboo transient transformation for the manipulation of hickory callus.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the functional role of proteins in gene regulation, TEA can also provide information on their subcellular locations and dynamics (i.e., their mobility) into the cell when protoplasts are expressing both the studied protein fused with a fluorescent one, such as YFP, GFP, CFP, or mCherry, and a fluorescent marker specific of a cellular compartment. To that end, several markers have been developed to mark specifically plant organelles ( Nelson et al, 2007 ; Zhang et al, 2021 ), and their diversity for the different organelles has been recently reviewed ( Zhu et al, 2020 ). These information may help to elucidate protein function ( Nelson et al, 2007 ), since TFs are expected to be found in the nucleus ( Asai et al, 2002 ; Sheikh et al, 2016 ; Moon et al, 2019 ), protein receptors in the PM ( Li et al, 2017 ; Liu et al, 2017 ; Pham et al, 2020 ), and proteins with a more versatile function can be found both in the cytosol and in cellular organelles ( Boudsocq et al, 2010 ).…”
Section: Protoplasts As Tools In Biomolecular Studiesmentioning
confidence: 99%